Анализ возможностей повторного эндодонтического лечения врачами стоматологических поликлиник Челябинской области на терапевтическом приеме (LLC "Endo Press", 2020)
According to the anonymous doctors questioning, the main causes of objective and subjective possibilities for re-intervention in root canals by physicians at a therapeutic dental reception in different dental clinics of Chelyabinsk city and Chelyabinsk region were studied in detail. The influencing factors for the physicians decision according using of the resorcinolformalin method were established.